2023
DOI: 10.1038/s41433-023-02615-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of retinal fluid monitoring in OCT imaging by automated deep learning versus human expert grading in neovascular AMD

Abstract: Purpose To evaluate the reliability of automated fluid detection in identifying retinal fluid activity in OCT scans of patients treated with anti-VEGF therapy for neovascular age-related macular degeneration by correlating human expert and automated measurements with central retinal subfield thickness (CSFT) and fluid volume values. Methods We utilized an automated deep learning approach to quantify macular fluid in SD-OCT volumes (Cirrus, Spectralis, Topc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Second, the absence of 3D volume measurements for both the retinal layers and fluid because of the need for multiple 2D scans and the segmentation of each image individually. Nevertheless, further investigation should consider seeking volumetric analyses, as previous studies have shown their valuable insights [34,35]. Third, this study was limited to diagnostic evaluation, as longitudinal follow-up data were not collected.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the absence of 3D volume measurements for both the retinal layers and fluid because of the need for multiple 2D scans and the segmentation of each image individually. Nevertheless, further investigation should consider seeking volumetric analyses, as previous studies have shown their valuable insights [34,35]. Third, this study was limited to diagnostic evaluation, as longitudinal follow-up data were not collected.…”
Section: Discussionmentioning
confidence: 99%